Catabolism of extracellular glutathione supplies cysteine to support tumours - Fabio Hecht; Marco Zocchi; Emily T. Tuttle; Nathan P. Ward; Fatemeh Alimohammadi; Amal Afzal Khan; Veronica C. Gomes; Bradley Smith; Jennifer J. Twardowski; Bradley N. Mills; Kevin A. Welle; Sina Ghaemmaghami; et al. (Nature, 2026)
Abstract Restricting amino acids from tumours is an emerging therapeutic strategy with substantial promise 1 . Although typically considered an intracellular antioxidant with tumour-promoting capabilities 2 , glutathione (GSH), as a tripeptide of cysteine, glutamate and glycine, can be catabolized to release amino acids. The extent to which GSH-derived amino acids are essential to cancers is unclear. Here we show that depletion of intracellular GSH does not alter tumour growth and extracellular GSH is highly abundant in the tumour microenvironment, highlighting the potential importance of GSH outside tumours. Supplementation with GSH rescues cancer cell survival and growth in cystine-deficient conditions, and this rescue depends on the catabolic activity of γ-glutamyltransferases. Finally, pharmacological targeting of the activity of γ-glutamyltransferases prevents the breakdown of circulating GSH, reduces tumour cysteine levels and slows tumour growth. Our findings indicate a non-canonical role for GSH in supporting tumours by acting as a reservoir of amino acids. Depriving tumours of extracellular GSH or inhibiting its breakdown is potentially a therapeutically tractable approach for patients with cancer. Furthermore, these findings change our view of GSH and how amino acids, including cysteine, are supplied to cells.